Komunikasi Pengasuhan Orang Tua pada Anak di Era Digital - Fitri Hardianti; Fatmawati, Fatmawati; Yuly Rahmi Pratiwi; Godefridus Samderubun (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Children are very familiar with various digital devices. Without adequate guidance from parents on the use of digital devices, this can certainly have fatal consequences for children. Digital devices have two different sides; on the one hand, they can bring positive things, but on the other hand, they can have negative effects. As parents, we should adjust our parenting styles to the behavioral tendencies of children who are attached to digital devices. The purpose of this study is to identify the dynamics of digital parenting communication and formulate patterns of digital parenting communication in Indonesia. The method used in this study is a narrative review. The results of the study show that, in general, parents in Indonesia have similar perceptions and concerns regarding the use of digital devices by their children. In communicating with their children, parents must first understand their role or position as creators of the digital environment, mediators, and actors in parenting. Parents are also required to be digitally competent, including in selecting, modifying, and managing content responsibly. Appropriate parenting communication for children in this digital era can be achieved by combining a number of strategies, including establishing open and honest communication, active restriction strategies, reactive intervention strategies, interpretation strategies, and the application of moral and religious values.